Las reglas de arbitraje de la CNUDMI frente al arbitraje en el sistema ecuatoriano - Ana Carolina Donoso Bustamante (Ius Humani. Jornal do direito, 2010)
It is a study of comparative law between the Arbitration Rules of the United Nations Commission for International Trade Law (UNCITRAL), specifically established in the Arbitration Rules, and the arbitration in Ecuadorian system. The paper first defines the concept of arbitration, international arbitration differentiating domestic arbitration. In a second time, there are a historical reference both as an institution and the UNCITRAL Arbitration Rules. Following, the author show a background study, Arbitration and Mediation Ecuadorian Law. Finally appears the comparation between the two systems, with the resulting conclusions.